Maternal outcomes of severe preeclampsia and eclampsia and associated factors among women admitted at referral hospitals of amhara regional state, institutional-based cross-sectional study, North-West Ethiopia - Melesse, Misganaw Fikrie; Aynalem, Getie Lake; Badi, Martha Berta; Aynalem, Bewket Yeserah (Frontiers in Global Women's Health, 2025)
IntroductionSevere preeclampsia/eclampsia is a multi-systemic pregnancy condition that manifests after 20 weeks of gestation and is linked to a high global rate of maternal morbidity and mortality. It is responsible for 11%–14% of maternal mortality globally and is the second most frequent direct obstetrical cause of death. This study aimed to assess maternal outcomes of severe preeclampsia/eclampsia and associated factors in mothers admitted to referral hospitals in the Amhara Regional State of North West Ethiopia.MethodsAn institutionally based cross-sectional investigation on the outcomes of severe preeclampsia/eclampsia in mothers was carried out from April 1 to September 30, 2018. Using the census sampling technique, 456 study participants were included in the study. Data were coded, verified, and imported into Epi-info version 7.2 before being exported and analyzed in SPSS version 26. To determine the determinants of maternal outcomes of severe preeclampsia or eclampsia, binary logistic regression was employed, with a significance level of 95% confidence interval of odds ratio at p-value 0.05 or below.ResultsOverall, severe preeclampsia and eclampsia were shown to have unfavorable maternal outcomes in 37.7% (95% CI: 32.8%, 42.3%). The following variables had statistically significant associations with unfavorable maternal outcomes of severe preeclampsia and eclampsia: educational status (AOR = 4.5, 95% CI: 1.95, 12.31), residence (AOR = 2.1, 95% CI: 1.17, 3.72), monthly family income (AOR = 2.7, 95% CI: 1.25, 6.12), parity (AOR = 6.7, 95% CI: 1.55, 12.6), history of abortion (AOR = 3.5, 95% CI: 1.63, 7.58), booking status (AOR = 5.8, 95% CI: 3.15, 9.72), and time of drug given (AOR = 4.9, 95% CI: 1.86, 13.22).ConclusionIt was discovered that severe preeclampsia and eclampsia had a high overall rate of unfavorable maternal outcomes. Promoting early antenatal care booking and formal education for women can reduce preeclampsia and eclampsia outcomes.